Beispiel Nr: 06
$ \text{Gegeben: } \text{ Punkt } A(xa/ya) \qquad \text{ Scheitel } S(xs /ys) \\ \text{Gesucht:} \\ y=ax^{2}+bx+c \\ \\ \text{Scheitel und Punkt}\\ \textbf{Gegeben:} \\ A(-2/-8)\qquad \text{ Scheitel } S(0/-3) \\\\ \\ \textbf{Rechnung:} \\ A(-2/-8)\qquad S(0/-3) \\ \text{Punkt A und Scheitel S in die Scheitelform einsetzen}\\ y=a(x-xs)^2+ys \\ -8=a(-2-0)^2-3 \\ -8=4\cdot a-3 \qquad /+3 \qquad /:4 \\ a=\frac{-8+3}{4} \\ a=-1\frac{1}{4} \\ y=-1\frac{1}{4}(x-0)^2-3 \\ y=-1\frac{1}{4}(x^2 -0 x+0^2)-3 \\ y= -1\frac{1}{4}x^2-3 $